The Effect Of Corporate Governance, Sharia Governance, And Risk Management On The Performance Of Islamic Banks In Africa - Muhammad, Aishatu Usman (2024)
Islamic Banking Has Become A Contemporary Topic Of Discussion Amongst Academics And Practitioners. This Relates To The Ongoing Global Financial Crises In Developing And Developed Nations. Islamic Banking In Africa Has Been In Existence For Decades; In Fact, The First Islamic Bank Was From Egypt. Despite Having The Second-Largest Muslim Population After Asia, Islamic Banking Performance Is The Lowest In Africa. Nonetheless, This Challenge Can Be Attributed To Governance And Risk Management, As Most Corporate Failures Are Attributed To Corporate Governance And Risk Management. In Addition To Corporate Governance, Islamic Banks Have Sharia Governance; These Guides Sharia Compliance In Their Operations And In Building Their Products, Which Is The Primary Distinction Between Islamic And Conventional Systems. Three Objectives Were Formulated For This Study To Accommodate These Problems. The First Objective Was To Analyse The Effect Of Corporate Governance On The Performance Of Islamic Banks In Africa. Secondly, To Examine The Effect Of Sharia Governance On The Performance Of Islamic Banks In Africa. Lastly, Investigate The Effect Of Risk Management On The Performance Of Islamic Banks In Africa. Panel Data Were Used In The Study From 2015 To 2020 For 28 Islamic Banks In Africa. A Correlational Research Design Was Used To Determine The Relationship Between The Variables. Data Was Collected Through Secondary Sources Via The Financial Statement Of The Banks. Panel Regression Analysis Was Used In Analysing The Data Using A Generalized Method Of Moment (Gmm) To Achieve The Stated Objectives.